2012
DOI: 10.1021/bi201787p
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Kinetic Mechanism of Inhibition of Elongation Factor 2 Kinase by NH125: Evidence of a Common in Vitro Artifact

Abstract: Evidence is emerging that elongation factor 2 kinase (eEF-2K) has potential as a target for anti-cancer therapy and possibly for the treatment of depression. Here the steady-state kinetic mechanism of eEF-2K is presented using a peptide substrate and is shown to conform to an ordered sequential mechanism with ATP binding first. Substrate inhibition by the peptide was observed and revealed to be competitive with ATP, explaining the observed ordered mechanism. Several small molecules are reported to inhibit eEF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 57 publications
1
68
0
Order By: Relevance
“…As potent small molecule inhibitors of eEF-2K are not currently available [57], we investigated the potential of targeting eEF-2K by siRNA. The delivery of therapeutics to tumor cells and vasculature is recognized as a potential approach for the treatment of cancer [29].…”
Section: Discussionmentioning
confidence: 99%
“…As potent small molecule inhibitors of eEF-2K are not currently available [57], we investigated the potential of targeting eEF-2K by siRNA. The delivery of therapeutics to tumor cells and vasculature is recognized as a potential approach for the treatment of cancer [29].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, NH125, an imidazolium derivative, was reported to be an eEF2K inhibitor [31] , but subsequent studies showed it actually increases eEF2 phosphorylation within cells, probably by acting as a non-specific protein-aggregating agent [32,33] . A thiopyran-dicarbonitrile analog was described as an eEF2K inhibitor by Devkota et al [34] .…”
Section: Inhibitors Of Eef2kmentioning
confidence: 99%
“…We expressed eEF-2K in Escherichia coli and purified it to homogeneity in a form free of phosphate that is capable of being stimulated by Ca 2ϩ /CaM to display high catalytic activity (33). This allowed us to identify five major Ca 2ϩ /CaM-stimulated autophosphorylation sites in eEF-2K (Thr-348, Thr-353, Ser-445, Ser-474, and Ser-500) (31) and characterize the kinetic mechanism for the phosphorylation of a peptide substrate (34). We found that Thr-348 is the first site to be autophosphorylated and is important for eEF-2K activation (31,33).…”
Section: Eef-2kmentioning
confidence: 99%